Local cost for global benefit: The case of wind turbines - Manuel Frondel; Gerhard Kussel; Stephan Sommer; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Given the rapid expansion of wind power capacities in Germany, this paper estimates the effects of wind turbines on house prices using real estate price data from Germany's leading online broker. Employing a hedonic price model whose specification is informed by machine learning techniques, our methodological approach provides insights into the sources of heterogeneity in treatment effects. We estimate an average treatment effect (ATE) of up to -7.1% for houses within a one-kilometer radius of a wind turbine, an effect that fades to zero at a distance of 8 to 9 km. Old houses and those in rural areas are affected the most, while home prices in urban areas are hardly affected. These results highlight that substantial local externalities are associated with wind power plants. – – Vor dem Hintergrund des starken Ausbaus der Windkraft in Deutschland schätzt dieses Papier den Effekt von Windkraftanlagen auf in der Umgebung befindliche Einfamilienhäuser auf Basis von rund 2,7 Mio. Immobilienofferten in Deutschlands größten Online-Portal, Immoscout 24. Mit Hilfe eines hedonischen Preismodells schätzen wir einen preissenkenden Effekt, der sich für Häuser, die sich in einem Radius von einem Kilometer von einer Windkraftanlage befinden, auf -7,1% beläuft. Der preissenkende Effekt wird mit zunehmendem Abstand von der Windkraftanlage kleiner und verschwindet gänzlich ab etwa 8 bis 9 Kilometer Abstand. Alte Häuser, die vor 1949 gebaut worden sind, und Häuser in ländlichen Regionen sind am stärksten betroffen, während die Häuserpreise in städtischen Gebieten weniger stark beeinflusst werden.
Keywords: Q21; D12; R31; 330; wind power; hedonic price model